Peningkatan Motivasi Belajar Melalui Pemanasan Permainan Pada Pembelajaran PJOK Kelas VII SMPN 1 Kota Kediri - Zulfa Oktari Rosyda; Mokhammad Firdaus; Danang Kanda Riyatmojo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to enhance students' learning motivation in Physical Education, Sports, and Health (PJOK) by implementing game-based warm-up methods at SMPN 1 Kota Kediri. The research employs Classroom Action Research (CAR) with two cycles, utilizing observation, documentation, and questionnaires for data collection. The results indicate that game-based warm-up methods positively contribute to increasing students’ motivation and engagement in PJOK learning. In the first cycle, 93.3% of students responded positively to the applied method, and in the second cycle, the number of students who strongly agreed increased from 50% to 70%, while those who disagreed decreased from 6.7% to 3.3%. These findings suggest that game variations, increased student interaction, and additional motivation can enhance PJOK learning effectiveness. This study recommends that teachers continue to develop game variations and create a more comfortable learning environment to accommodate students' needs optimally.